The Influence of Teaching Practices and Teacher Professional Perceptions on Readiness to Become a Teacher: Teacher Interest as a Mediating Variable - Tarisa Eka Dwiyanti Lailatul Rokhma; Jun Surjanti (Jurnal Studi Guru dan Pembelajaran, 2025)
The most students pursuing undergraduate degrees in Economics education are hesitant to pursue a career in teaching, primarily due to inadequate preparation and a lack of interest in the teaching profession after completing their undergraduate studies. This study aims to determine the influence of teaching practices, perceptions of the teaching profession, and teaching interest on students' readiness to become teachers. This study also examines whether teaching interest has a mediating effect in this relationship. Using a quantitative approach and involving 106 Economics Education students at the Faculty of Economics and Business, Semarang State University (UNESA) were selected used proportional random sampling. Data were collected through questionnaires and analyzed using SEM-PLS. The results showed that teaching practices and students' perceptions of the teaching profession had a significant on their readiness to become teachers (p-value < 0.05). However, teaching interest did not significantly influence readiness itself (p-value = 0.170), nor did it mediate the influence of other factors (p > 0.05). The current study can be a reference for building professional readiness of teachers that is more contextual to educational needs and pays attention to teaching practices as a dominant factor in improving readiness to become and encourage the development of a new conceptual framework that combines affective, cognitive, and empirical aspects in a more balanced way in explaining readiness to become teachers.